Pest Control Strategies in Hotel: A Case of Kathmandu Valley - Acharya, Sandesh (Nepalese Journal of Management, 2024)
This study examines the pest control strategies in hotel: A case of Kathmandu Valley. Customer health is the dependent variable. The selected independent variables are type of pests, pest infestation level, building and room design, cleaning and maintenance practices, environmental factor, pest control products and methods. The primary source of data is used to assess the opinions of the respondents regarding type of pests, pest infestation level, building and room design, cleaning and maintenance practices, environmental factor, pest control products and methods. The study is based on primary data of 100 respondents. To achieve the purpose of the study, structured questionnaire is designed. The regression models are estimated to test the significance and importance of pest control strategies in hotel: A case of Kathmandu Valley.The study shows that types of pests is positively correlated to customer health. It indicates that different types of pests used by the hotels leads to reduce health related issues. Similarly, pest infestation level is positively correlated to customer health. It indicates that as the level of pest infestation increases, the risk of customer health problems also increases. Likewise, building and room design is positively correlated to customer health. It indicates that a well-designed buildings and rooms can have positive impact on customer health. Further, cleaning and maintenance is negatively correlated to customer health. It indicating that by cleaning and disinfecting surfaces regularly, businesses can help to reduce the number of germs and bacteria which can lead to reduce number of health problems. In addition, environmental factor is negatively correlated to customer health. It indicates that exposure to excessive noise levels, whether from traffic, industrial activities, or construction sites, can have negative effects on health. Moreover, pest control products and methods are also positively correlated to consumer health. It indicates that high quality product used for germ and bacteria leads to reduce issues related to customer health.